A novel approach for metabolic pathway optimization: Oligo-linker mediated assembly (OLMA) method. Issue 1 (December 2015) - Zhang, Shasha; Zhao, Xuejin; Tao, Yong; Lou, Chunbo
Abstract Background Imbalances in gene expression of a metabolic pathway can result in less-yield of the desired products. Several targets were intensively investigated to balance the gene expression, such as promoter, ribosome binding site (RBS), the order of genes, as well as the species of the enzymes. However, the capability of simultaneous manipulation of multiple targets still needs to be explored. Results We reported a new DNA assembling method to vary all the above types of regulatory targets simultaneously, namedo ligo-l inkerm ediateda ssembly (OLMA) method, which can incorporate up to 8 targets in a single assembly step. Two experimental cases were used to demonstrate the capability of the method: (1) assembly of multiple pieces oflac Z expression cassette; (2) optimization of four enzymes in lycopene biosynthetic pathway. Our results indicated that the OLMA method not only exploited larger combinatorial space, but also reduced the inefficient mutants. Conclusions The unique feature ofo ligo-l inkerm ediateda ssembly (OLMA) method is inclusion of a set of chemically synthetic double-stranded DNA oligo library, which can be designed as promoters and RBSs, or designed with different overhang to bridge the genes in different orders. The inclusion of the oligos resulted in a PCR-free and zipcode-free DNA assembly reaction for OLMA.